Akselerasi Kemampuan Sumber Daya Manusia Sebagai Upaya Diversifikasi Produk Unggulan Sentra Industri Tape Desa Banjarsari Melalui Pelatihan Diversifikasi Produksi Pancake Tape - Linda Agustin Ningrum; Alby Aruna; Eka Putri Surya; Abdul Rahman Prasetyo; Adinda Marcelliantika; Ginanjar Atma Wijaya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Accelerating human resource capabilities as an effort to diversify flagship products of the Tape Industry Center in Banjarsari Village through Pancake Tape production training aims to enhance local producers' skills and knowledge in developing new products. This program involves technical training and recipe development for Pancake Tape, integrating tape as the main ingredient with modern pancake-making techniques. Methods include workshops, live demonstrations, and production outcome evaluations. Results indicate a significant improvement in production skills and innovation capabilities of local producers. The implementation of this program is expected to support product diversification, increase competitiveness, and expand the market of the Tape Industry Center in Banjarsari Village.